MAMPUKAH STRUKTUR MODAL MEMEDIASI PENGARUH CEO NARCISSISM DAN OVERCONFIDENCE TERHADAP KINERJA PERUSAHAAN? - Candy Candy; Delfina Delfina (Jurnal Akuntansi dan Keuangan (JAK), 2023)
CEOs in corporations may not always employ logical reasoning when making decisions and may be swayed by personal characteristics such as overconfidence and narcissism. The decisions made by CEOs ultimately affect the company's performance. This study examines how CEO overconfidence and narcissism affect firm performance in the presence of capital structure variables. The study surveyed 39 infrastructure companies listed on the Indonesia Stock Exchange between 2017 and 2021, totaling 175 observations. The data were analyzed using Stata 16 to test the direct effect, and indirect effects were tested using the Sobel test. Results indicate that neither CEO overconfidence nor narcissism has a significant impact on a firm's performance, as measured by ROA or ROE. Furthermore, CEO narcissism has no impact on firm performance mediated by capital structure, while capital structure can mediate the effect of CEO overconfidence on ROA but not on ROE